In Melbourne tonight: Pop/rock histories and futures. (23rd June 2017) - Homan, Shane; O'Hanlon, Seamus; Strong, Catherine; Tebbutt, John
Abstract : In recent decades the 'music city' has emerged as an important series (and exchanges) of representations, capital, labour, sounds and commodities. City heritage and histories—particular narratives of music development, genres, venues and personnel—continue to inform contemporary city branding, tourism and industrial strategies. This article explores how both the practices and discourses of the 'music city' circulate in terms of specific histories, and how, in turn, they might inform contemporary practices and future intent. Melbourne, the self-proclaimed music and cultural capital of Australia, is examined as a case study in how the past and present circulate. The article also explores the challenges in documenting the emergence and development of popular music in Melbourne from the 1950s to the present as a three-year Australian Research Council Discovery project, Interrogating the Music City: Cultural Economy and Popular Music in Melbourne, funded from 2016 to 2018.